Effects of ClO2 fumigation on postharvest fungi and disease development of longan fruit - A. Chumyam (2018)
The effect of chlorine dioxide (ClO < inf > 2 < /inf > ) fumigation on postharvest diseases of longan fruit 'Daw' during storage at room temperature was investigated. Fresh longan fruit were fumigated with 0 (control), 2.5, 5, 10 and 25 mg/L ClO < inf > 2 < /inf > for 10 min, then packed in cardboard boxes and stored at 25±1°C for seven days. ClO < inf > 2 < /inf > significantly reduced and delayed the occurrence of disease and total microbial load in all treatments. ClO < inf > 2 < /inf > at the concentrations of 10 and 25 mg/L were most effective with no difference in both disease incidence and total microorganisms. On day 7 of storage, treatment with 10 and 25 mg/L ClO < inf > 2 < /inf > reduced the total microorganisms by 81.5 and 83.2%, respectively. In the second experiment, the effect of ClO < inf > 2 < /inf > fumigation with 0 (control) and 10 mg/L ClO < inf > 2 < /inf > for 10 min and kept at room temperature for seven days on the growth of Cladosporium sp., Lasiodiplodia sp. and Fusarium sp. isolated from longan fruit and cultured on potato dextrose agar were determined. It was shown that ClO < inf > 2 < /inf > treatment significantly reduced growth of the three fungi. On day 7, ClO < inf > 2 < /inf > fumigation inhibited growth of Cladosporium sp., Lasiodiplodia sp. and Fusarium sp. by 96.7, 87.4 and 31.2% respectively.